Early Effects of Improved Mood on Propensity for Emotional Eating During the Physical Activity-only Phase of a Community-Based Behavioral Treatment for Obesity in Women with High Mood Disturbance - James J. Annesi; Amelia A. Eberly (New Prairie Press, 2022)
Weight loss beyond the short term is problematic for individuals with obesity. Especially for women, emotional eating is one of the greatest barriers and might require attention early in a behavioral weight- loss program. Physical activity-associated mood improvement may be associated with reduced emotional eating. Women with obesity volunteered for a community-based weight-management treatment. Effects associated with the initial 10 weeks, which focused on behavioral support of physical activity (prior to addressing eating behavior change), were assessed. Groups were designated based on whether participants' high total mood disturbance (TMD) scores reduced to a normal level (n = 45) or remained high (n = 27). Although significant overall improvements in emotional eating were found, F(1, 70) = 22.80, p < .001, its change scores did not significantly differ by group, F(1, 70) = 0.82, p = .370. Using aggregated data, the prediction of reduction in emotional eating by lowered TMD scores was not statistically significant. Adding change in self-efficacy for controlled eating into Step 2 of the regression model significantly increased the explained variance to R2 = .10, p = .014, with group not being a significant contributor when added in Step 3. TMD reduction was significantly predicted by increase in physical activity, β = -.23, p = .028, and completion of at least 3 bouts/week, rpb = -.22, p= .015. Because physical activity-related reductions in negative mood and increases in self-efficacy were associated with reduced emotional eating, viability for those behavioral factors as early treatment targets were signaled.